ANALISIS MANAJEMEN PELAYANAN HAJI DALAM MENINGKATKAN KEPUASAN JAMAAH PADA KEMENTERIAN AGAMA KABUPATEN SIJUNJUNG - Sindy Aidil Fitri; Khadijah Nurani (CV. Adiba Aisha Amira, 2023)
The background of this thesis is that the Ministry of Religion of Sijunjung Regency has problems with the room facilities for services that are not extensive enough, resulting in prospective pilgrims who wish to register having to wait outside the room for the Hajj and Umrah Organizing section when many pilgrims come to request services and elements of continuous improvement where is the lack of manpower or employees in the Hajj and Umrah Organizing Section of the Ministry of Religion of Sijunjung Regency. The purpose of this study is to find out and analyze a large part of the Management Analysis of Hajj Services in Improving Pilgrimage Satisfaction at the Ministry of Religion of Sijunjung Regency. This study uses a qualitative descriptive research method by collecting observation, interview and documentation methods. The results of this study indicate that Service Management has indicators in the form of polite behavior, method of delivery, time of delivery and hospitality. From these factors, the results of an assessment of the Service Management implemented by the Ministry of Religion of Sijunjung Regency were obtained in the Hajj and Umrah Organizing Section. Hajj and Umrah Management Employees have clear service standards and have guarantees for the privacy of pilgrims. The facilities and infrastructure provided are adequate. Employees serve the congregation not only in the office but also provide services via telephone so that they can quickly and responsively respond to problems or problems experienced by the congregation.